(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2025)
Edge-enabled Vehicular Ad Hoc Networks (VANETs) provision real-time services, storage, computation, and communication facilities to vehicles through Roadside Units (RSUs). Nevertheless, RSUs are often easy targets for security assaults due to their resource-constrained nature and placement in an open, unprotected environment. The compromised RSUs impede the VANET operations, causing traffic mismanagement and threats to human safety. Hence, an effective malicious RSU detection mechanism is crucial for VANETs. More specifically, a mechanism to detect the misbehavior of RSUs on RSU-to-RSU (R2R) communications, essential for message forwarding, beacon message sharing, and traffic alert sharing among RSUs, needs to be included. Besides, current works use only vehicle speed and density in beacon messages to assess trust without considering the sensor-detected data in the same messages. Nonetheless, sensor data is useful for traffic management, and neglecting them creates inaccuracy in trust estimation. This paper addresses these limitations and proposes a trust-based scheme to detect malicious RSUs that uses R2R interaction to analyze an RSU’s behavior. We also offer a mechanism to detect alteration of sensor-detected data in beacon content and incorporate this scheme in the trust calculation of RSUs. The experimental results show that the proposed solution effectively detects approximately 92% malicious RSUs, even in the presence of hostile vehicles. Moreover, integrating the proposed solution with the VANET routing protocols improves routing efficiency. J. Asiat. Soc. Bangladesh, Sci. 51(1): 123-150, June 2025